Implementation of Contextual Teaching and Learning Model to Improve Fifth Grade Students’ Mathematical Concept Understanding at SDN 54 Kalosi - Musdalipa Chairi Hamsah; Jonathan S Pasinggi; Abd. Halik (Darul Yasin Al Sys, 2026)
Although the implementation of innovative learning models in elementary mathematics education has received increasing attention, research specifically examining the effectiveness of the Contextual Teaching and Learning (CTL) model in improving fifth-grade students’ conceptual understanding in rural elementary schools remains limited. This study aims to evaluate the effectiveness of the CTL model in enhancing students’ understanding of mathematical concepts. A qualitative approach was employed using a Classroom Action Research (CAR) design involving 10 fifth-grade students (5 males and 5 females) of UPTD SD Negeri 54 Kalosi selected through purposive sampling. Data were collected through observation, tests, reflection notes, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that students’ conceptual understanding improved substantially across two instructional cycles: in Cycle I, the average score reached 74% with 40% learning mastery and the learning process categorized as sufficient, whereas in Cycle II the learning process improved to a good category, with the average score increasing to 84% and learning mastery reaching 90%. These results contribute to the theoretical development of contextual learning theory in mathematics education and extend understanding of its practical implementation in rural elementary school settings. The study concludes that the CTL model plays a crucial role in strengthening students’ conceptual understanding in mathematics learning and recommends that teachers systematically integrate contextual strategies into classroom instruction. The implications include theoretical contributions to the growing literature on contextual mathematics learning and practical guidance for elementary school educators, while future research is encouraged to explore the broader application of CTL across diverse educational contexts and larger student populations.